The Yeast F-Box Protein Met30 Regulates Proline Utilization Independently of Transceptor Can1 Under Nutrient-Rich Conditions - Akira Nishimura; Ryoya Tanahashi; Hiroshi Takagi (Microorganisms)
Proline is the most abundant amino acid in wine and beer, largely due to the limited utilization of proline by the yeast Saccharomyces cerevisiae during fermentation. Previous studies have shown that the arginine transporter Can1 plays a role in regulating proline utilization by acting as a transceptor, combining the functions of both a transporter and a receptor for basic amino acids. However, the CAN1-disrupted strains have exhibited the inhibition of proline utilization under nutrient-rich conditions, indicating that additional factors beyond basic amino acids contribute to the inhibition of proline utilization. Here, we used the parent strain with the CAN1 deletion to derive mutants that can utilize proline even under nutrient-rich conditions. A genomic analysis revealed a mutation in the MET30 gene, which encodes an F-box subunit of the SCF ubiquitin ligase complex, that causes reduced Met30 function. Importantly, we found that Met30 and Can1 independently regulate proline utilization. Our screening showed that the Met30-dependent inhibition of proline utilization occurs when ammonium ions, methionine or cysteine, and another amino acid (especially threonine or isoleucine) are present simultaneously. The present data offer new insights into the regulation of proline metabolism.